Once upon a Marigold - Ferris, Jean, 1939- (San Diego : Harcourt, Inc., 2002)
A young man with a mysterious past and a penchant for inventing things leaves the troll who raised him, meets an unhappy princess he has loved from afar, and discovers a plot against her and her father.
Accelerated Reader/Renaissance Learning
Keywords: Princesses -- Fiction; Families -- Fiction; Trolls -- Fiction; Fairy tales; Fantasy fiction